Treatment and complications of orbito-zygomatic fractures - Trindade, Paulo Alceu Kiemle; Vieira, Eduardo Hochuli [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP]; Gabrielli, Mario Francisco Real [UNESP]; Pereira Filho, Valfrido Antonio [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2012)
The aim of the present study was to analyze the etiology, type and treatment employed in the orbito-zygomatic fractures (OZ). Also, postoperative complications are described and correlated with the type of treatment used. Fifty patients with OZ fractures were evaluated. Orbital fractures in which the zygomatic bone was not involved were excluded. Epidemiologic data and characteristics of treatment such as the type of material used for osteosynthesis, number of anatomical sites on which rigid internal fixation (RIF) was applied, surgical approaches and associated complications were recorded. The main causes of trauma were motorcycle and bicycle accidents, constituting 52% of the sample. The osteosynthesis system used was the 2.0 mm, except in four patients in whom the 1.5mm system was used for fixation at the infra-orbital rim. A total of 18% of the patients required reconstruction of the internal orbit and in all cases titanium mesh was used. 46% of the patients received RIF in three anatomical sites, most in the fronto-zygomatic suture, infra-orbital rim and zygomatic-maxillary buttress. The most frequent complication was paresthesia of the infra-orbital nerve (34 patients, 68%). Other findings were also discussed with the intent of better understanding the treatment of the OZ fractures.

El objetivo del presente estudio fue analizar la etiología, tipo y tratamiento empleado en las fracturas órbito-cigomáticas (OC). Además, se describen y correlacionan las complicaciones postoperatorias con el tipo de tratamiento utilizado. Cincuenta pacientes con fracturas OC fueron evaluados. Las fracturas orbitarias en la que el hueso cigomático no participó fueron excluidas. Los datos epidemiológicos y las características de tratamiento, tales como el tipo de material utilizado para la osteosíntesis, número de sitios anatómicos en los que se aplicó la fijación interna rígida (FIR), enfoques quirúrgicos y complicaciones asociadas fueron registrados. Las principales causas de los traumas fueron accidentes de bicicleta y motocicleta, constituyendo el 52% de la muestra. El sistema de osteosíntesis utilizado fue de 2,0 mm, excepto en cuatro pacientes en los que se utilizó el sistema de 1,5 mm para la fijación en el borde infraorbitario. El 18% de los pacientes requirieron reconstrucción de la órbita interna y en todos los casos se utilizó malla de titanio. El 46% de los pacientes recibió FIR en tres sitios anatómicos, la mayoría en la sutura fronto-cigomático, borde infraorbitario y pilar cigomato-maxilar. La complicación más frecuente fue parestesia del nervio infraorbitario (34 pacientes, 68%). Otros hallazgos fueron discutidos con la intención de comprender mejor el tratamiento de las fracturas OC.
Tratamiento y complicaciones de las fracturas órbito-cigomáticas
Keywords: Zygoma; Orbit; Facial fractures; Hueso cigomático; Órbita; Fracturas faciales